Formulation and In-Vitro Evaluation Curcumin Ovule with Polyethylene Glycol (Peg) Base - Delarosa, Dathin Aulia; S, Sumaiyah; Hasibuan, Poppy Anjelisa Z. (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: This study aims to formulate and in vitro evaluation curcumin ovule with polyethylene glycol bases 400 and 6000 concentration variation using fushion method. Method: Curcumin ovule formulated by fushion method using the comparison of polyethylene glycol 400 and 6000 base concentration. In vitro evaluation of preparations included observation of organoleptic (odor, color, and shape), measurement of uniformity of weight, disintegration time, observation of stability of the preparation during 6 months storage at refrigerator temperature, and release test. Results: The results showed that all preparations ovule curcumin were orange, specific odor, cone-shape, stable for 6 months storage at refrigerator. Uniformity of ovule weight and disintegration time according the standard prepaation. Ovule release test showed formula I polyethylen glycol base concentration of 400 (90%) and 6000 (10%) very fast to release of curcumin from the preparation compared to other formula is gave average release of 93,7% ± SD 0.36. Conclusion: Curcumin can be formulated in the form of ovule using polyethylene glycol bases 400 and 6000 concentration variation.